Does gender diversity on corporate boards reduce information asymmetry in equity markets? - David Abad Díaz; María Encarnación Lucas-Pérez; Antonio Minguez-Vera; José Yagüe Guirao (BRQ Business Research Quarterly, 2017)
We examine the relation between the gender diversity on boards of corporations and the levels of information asymmetry in the stock market. Prior evidence suggests that the presence of women on director boards increases the quantity and quality of public disclosure by firms, and we therefore expect firms with higher gender diversity on their boards to show lower levels of information asymmetry in the market. Using a Spanish sample, proxies for information asymmetry estimated from high-frequency data along with system GMM panel methodology, we find that the gender diversity on boards is negatively associated with the level of information asymmetry in the stock market. Our findings support the changes in the laws that have been introduced in several countries to increase the proportion of female company directors by providing evidence that gender diverse boards have beneficial effects on stock markets."
Keywords: 650; Corporate board; Female directors; Gender diversity; Information asymmetry; Market microstructure